Gender Gap in Academic Achievement in Brunei Tertiary Education: Qualitative Perspective - Metussin, Halimaturradiah (European Journal of Social Science Education and Research, 2018)
This study explores the potential factors causing a gender gap in academic achievement in the higher learning institutions of Brunei using in-depth interviews. Given that the gender gap is a worldwide phenomenon and problem in many educational settings, this study investigates the reasons for its persistence and how it can be resolved in the Brunei context. The findings of the study indicate that: 1) there are gender similarities in practices of good academic performance at school; 2) teaching methods and school facilities and environment may affect students’ academic performance; 3) problems or challenges faced in academic performance or achievement at school; and 4) early entry to workplace. A mixed-methods research is recommended to gain additional insights into the problem and its solutions.
Keywords: Gender gap, academic achievement, gender differences, tertiary education, qualitative methods.